Gut microbiota of adults with asthma is broadly similar to non-asthmatics in a large population with varied ethnic origins. (1st January 2021) - Kullberg, Robert F. J.; Haak, Bastiaan W.; Abdel-Aziz, Mahmoud I.; Davids, Mark; Hugenholtz, Floor; Nieuwdorp, Max; Galenkamp, Henrike; Prins, Maria; Maitland-van der Zee, Anke H.; Wiersinga, W. Joost
ABSTRACT: Bacterial gut communities might predispose children to develop asthma. Yet, little is known about the role of these micro-organisms in adult asthmatics. We aimed to profile the relationship between fecal microbiota and asthma in a large-scale, ethnically diverse, observational cohort of adults. Fecal microbiota composition of 1632 adults (172 asthmatics and 1460 non-asthmatics) was analyzed using 16S ribosomal RNA gene sequencing. Using extremely randomized trees machine learning models, we assessed the discriminatory ability of gut bacterial features to identify asthmatics from non-asthmatics. Asthma contributed 0.019% to interindividual dissimilarities in intestinal microbiota composition, which was not significant ( P = .97). Asthmatics could not be distinguished from non-asthmatics based on individual microbiota composition by an extremely randomized trees classifier model (area under the receiver operating characteristic curve = 0.54). In conclusion, there were no prominent differences in fecal microbiota composition in adult asthmatics when compared to non-asthmatics in an urban, large-sized and ethnically diverse cohort.